2014
DOI: 10.1108/ijmpb-10-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

The problem of rape in India: a multi-dimensional analysis

Abstract: Purpose – The purpose of this paper is to analyse the problem of “Rape” in India from multiple perspectives and recommend measures for mitigating this crime from the country. Using the much highlighted incident of gang rape of a 23-year-old woman in Delhi, India on 16 December 2012, the paper analyses the behaviour of the various parties involved in the case with the help of some sociological and psychological theories. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In contrast to study of Cheung and Hwang (2004), violent sexual activities like rape were mostly associated with asphyxia or road/railway accidents in females of the younger age group in India (Cheung and Hwang 2004;Sharma et al 2014;Madan and Sinha 2013;Crime in India 2012. Females at the age of 10-29 years are more susceptible to the major curses of our society such as rape and Bdowry death^.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to study of Cheung and Hwang (2004), violent sexual activities like rape were mostly associated with asphyxia or road/railway accidents in females of the younger age group in India (Cheung and Hwang 2004;Sharma et al 2014;Madan and Sinha 2013;Crime in India 2012. Females at the age of 10-29 years are more susceptible to the major curses of our society such as rape and Bdowry death^.…”
Section: Discussionmentioning
confidence: 60%
“… 38 Rape and other forms of sexual violence against women remain a taboo topic because not only does it result in physical harm of the victim, but it also disgraces and tarnishes the victim's psyche with devastating effect. 39 With family members reported to be the most common perpetrators of sexual violence against women, 40 the social implications and associated stigma of reporting such cases are even higher. In light of the current increased visibility of the issue, and dramatic upsurge in cases of sexual violence against women being reported, we as researchers are faced with the dilemma of either providing a means to shed light on this highly relevant issue, or comply with social customs and further fuel the stigma and lack of awareness by discounting the problem.…”
Section: Discussionmentioning
confidence: 99%
“…She told police that advocate borrowed money sometime ago. Now when I asked for money, he abused me and threatens to kill me (Dainik Jagran: Kanpur, July 24,2012)." This is a significant finding as the elderly women have, in general, relied upon the family members and relatives for physical and mental support.…”
Section: Victim-offender Relationshipmentioning
confidence: 99%
“…Moreover, the study has pointed out through news items that technological innovation, urbanisation and migration have significantly affected our value based social system because these changes have brought the technological innovation. This technological innovation has exposed individual to all kinds of violent behaviours and abusive behaviours which are the major factors behind the crime against elderly women [23,24]. Further, the study has found that that economic growth has brought to India problems inherent to rapid urbanisation and migration which have affected the contemporary way of life.…”
Section: Victim-offender Relationshipmentioning
confidence: 99%
See 1 more Smart Citation